Synthesis and mechanism study of Au nanowires and their derivatives - Wang, Yawen (2015)
This thesis summarizes my postgraduate research on the mechanism studies of the novel nanowire and nanowire related structures, rational design and synthesis based on the mechanism understanding, and structural transformation at the nanoscale. The research was carried out mostly based on the ultrathin gold nanowires (Au NWs) structures. Two main systems were studied: the Active Surface Growth mechanism which yields then substrate-bound Au nanostructures and the ultrathin Au NWs synthesized in the in the colloidal organic mediate. We systematically studied Active Surface Growth mechanism, and demonstrated it to be an effective method for enriching the synthetic capability of the Au nanostructures. On the other hand, gold and silver (Ag) was grown onto the colloidal ultrathin Au NWs, giving novel nanobracelets structures and alloy wires with novel twisting morphologies.